Albanian Customary Law, Religion, and the Rescue of Jews during the Holocaust - Malaj, Visar (Holocaust and genocide studies, 2022)
Albania was the only German-occupied country in which the number of Jews increased after World War II. Almost all native Jews of Albania survived the Holocaust, and thousands of Jewish refugees from other European countries were assisted and protected during the years 1933-1945. The rescue was facilitated by a unique mixture of factors, but the main common motivation of Muslim, Catholic, and Orthodox rescuers was Besa, the crucial element of Kanun, the Albanian customary law.